Implementasi Outing Class TK Prime Kids Padang di Rumah Sakit Gigi dan Mulut Pendidikan Baiturrahmah: indonesia - Rahmaningseh, Fitria; Maharani, Frisca; Surya, Leny Sang; Zia, Hanim Khalida; Pertiwi, Oniel Syukma; Pujiyati, Alfiyah (UII, 2025)
Education is an endeavor that refers to the noble values that are part of the nation's life, by which these values can be continued through the role of educational transfer in both cognitive, attitudinal and skill aspects. One way to obtain educational values is by conducting outdoor learning activities (outing class). Outing class is an educational program that is one of the school programs in an effort to build the character of school children, especially the character of the nation where the outing class program is a direct and real morally charged character education learning that invites children to learn directly about the object of learning. The purpose of this activity is to develop children's level of knowledge and interest in learning outside of school. The methods used in this activity are based on observation, interviews and direct documentation in the field. The subjects of this activity amounted to 65 TK children and 9 mentoring teachers. This Outing class activity gives the impression of an extraordinary and fun experience for Prime Kids TK children at the Baiturrahmah Educational Dental and Oral Hospital.